From Moderates to Extremes: How Immigration Polarizes American Politics - Johannes Matzat; Axel Dreher; Sarah Langlotz; Christopher Parsons (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
We provide causal evidence that immigration has contributed to the polarization of American politics. Using an ancestry-based shift-share instrument, we study immigration flows into U.S. counties between 1992 and 2016. Counties exposed to larger immigrant inflows become more polarized both in campaign contributions and in political representation: donors increasingly support ideologically extreme candidates for the U.S. House of Representatives, and the candidates who win office are themselves further from the ideological center. These effects are most pronounced in primary elections, where moderate Democrats are more likely to lose and conservative Republicans more likely to win in counties with higher immigration inflows. The rightward shift is strongest in occupations with high immigrant shares but limited interpersonal contact, suggesting that exposure without interaction amplifies perceived threat. We complement these results with original survey evidence that sheds light on the underlying mechanisms. Liberals and conservatives differ less in their economic assessments of immigration than in their cultural interpretations: liberals stress diversity and opportunity, whereas conservatives emphasize risk and social cohesion. Together, these findings indicate that immigration reshapes American politics through the joint forces of salience and contact – heightening polarization where immigrants are visible but unfamiliar, and attenuating it where interaction is routine.
Keywords: J15; F52; F63; 330; migration; polarization; political ideology; United States